Socialization of the Kaffir Lime Plants as a Potential Source of Essential Oils in the Community of Mandor Village, Mandor District, Landak Regency, West Kalimantan - Yeni Mariani; Fathul Yusro; Hikma Yanti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Essential oil is a type of NTFP with a high economic value produced by plant parts such as leaves, fruit, seeds, flowers, roots, rhizomes, bark, and all parts of the plant. Kaffir lime (Citrus hystrix) is one type of essential oil-producing plant that can be cultivated in the surrounding environment (yard, garden) or less productive land so that it has added value. Kaffir lime is a spice or food flavouring with a distinctive aroma and taste due to the presence of citronellal and is used in the perfume and cosmetic industries. This plant can be an opportunity for the community, especially those near the forest, to improve their welfare by cultivating it as a source of essential oils. The purpose of this community service activity is to provide information on the potential of kaffir lime as an essential oil producer to open the insight of the Mandor village community to cultivate kaffir lime plants. The target of this activity is the Mandor village community. We conducted this from May to November 2021, including the preparation and production stages, the essential oil's chemical content and antibacterial analysis, and the delivery of socialization. The socialization activity was evaluated before and after the action by measuring the knowledge of the village community regarding essential oils and kaffir lime. The results of the action conveyed information on the potential of the kaffir lime plant as a source of essential oil, the process of making essential oil, the results of testing on the content contained in kaffir lime essential oil, antibacterial activity, the form of its use in various products of economic value as well as basic information on the cultivation of this plant.